2019
DOI: 10.2140/akt.2019.4.151
|View full text |Cite
|
Sign up to set email alerts
|

G-theory of root stacks and equivariant K-theory

Abstract: Using the description of the category of quasi-coherent sheaves on a root stack, we compute the G-theory of root stacks via localisation methods. We apply our results to the study of equivariant K-theory of algebraic varieties under certain conditions. Proof. This follows by combining Corollaries 3.10 and 3.15. So we have:G(X L, r ) ∼ = K(EP(X, L, r)), and we reduced the problem to describing the K-theory of the (abelian) category of coherent extendable pairs EP(X, L, r).We are going to use several splittings … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…For each of the stars in our sample we determine the rotational period, Prot, initially using the Period (Dhillon et al 2001) software package which runs a Lomb-Scargle (LS) periodogram, followed by an iterative process involving the phase folding of sections from the start and end of the lightcurve. Phase zero, φ0, is also defined as the minimum of the flux of the rotational modulation which is initially determined by eye.…”
Section: Rotation Periodmentioning
confidence: 99%
“…For each of the stars in our sample we determine the rotational period, Prot, initially using the Period (Dhillon et al 2001) software package which runs a Lomb-Scargle (LS) periodogram, followed by an iterative process involving the phase folding of sections from the start and end of the lightcurve. Phase zero, φ0, is also defined as the minimum of the flux of the rotational modulation which is initially determined by eye.…”
Section: Rotation Periodmentioning
confidence: 99%
“…The herbal samples of CI used in this study were characterized by 9.1±0.48% water content and caused significant changes in the water absorption capacity of the bread sample, which was evident by farinograph studies which showed an increase in absorption from 60.0% to 65.4%. Other studies reported that oregano addition to bread formulation increased the water absorption capacity and dough development time, which was associated with a significant decrease in dough stability [20].…”
Section: Physical Properties Of Bread Fortified With Cistus Incanusmentioning
confidence: 95%
“…Antioxidative potential of bread was also improved by green tea powder, herbs, and tomato paste [19]. Bread supplemented with 1%, 2%, 3%, and 4% oregano samples showed high TPC and radical scavenging activity [20]. Black tea incorporation enhanced the antioxidant activity of Chinese steamed wheat bread [47].…”
Section: Total Phenolic Content and Antioxidant Activity Of Bread Incmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,9] Among biological methods, the mycogenic synthesis of nanoparticles have been widely documented. [10][11][12] This mycogenic synthesis can easily achieve novel NPs which are environmentally safer and effectively used for broad spectrum of medical and agriculture applications. [1,2,6,7] However, the mass production of microorganisms is time consuming and expensive compared to the plant extracts production.…”
Section: Introductionmentioning
confidence: 99%